2018
DOI: 10.1088/1361-6382/aaa279
|View full text |Cite
|
Sign up to set email alerts
|

Atomic clock ensemble in space (ACES) data analysis

Abstract: The Atomic Clocks Ensemble in Space (ACES/PHARAO mission, ESA & CNES) will be installed on board the International Space Station (ISS) next year. A crucial part of this experiment is its two-way MicroWave Link (MWL), which will compare the timescale generated on board with those provided by several ground stations disseminated on the Earth. A dedicated Data Analysis Center (DAC) is being implemented at SYRTE -Observatoire de Paris, where our team currently develops theoretical modelling, numerical simulations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…Once the MWL time transfer software was developed, the impact on time transfer was addressed numerically with the MWL software itself, with several levels of uncertainty of a real ISS orbitography file. It showed that below 1 km orbit error the impact is below specifications [17], confirming the estimates in [18] for the time transfer part.…”
Section: Estimation Of the Orbitography Uncertainty Requirementsupporting
confidence: 73%
See 3 more Smart Citations
“…Once the MWL time transfer software was developed, the impact on time transfer was addressed numerically with the MWL software itself, with several levels of uncertainty of a real ISS orbitography file. It showed that below 1 km orbit error the impact is below specifications [17], confirming the estimates in [18] for the time transfer part.…”
Section: Estimation Of the Orbitography Uncertainty Requirementsupporting
confidence: 73%
“…In the ACES mission, a given ground clock in a laboratory equipped with a MWL ground terminal will be compared to PHARAO when ISS is in sight. The time transfer software for extracting the clock desynchronization from MWL raw data has been presented in [17].…”
Section: Aces Datamentioning
confidence: 99%
See 2 more Smart Citations
“…A possibility along this line is offered by the hydrogen atoms for which the interaction between electron and proton magnetic moments induces a split in two levels of the 1s ground-state; this kind of atomic clock has been also used by Galileo [15] and ACES [16]. The sum of the angular moments of electron and proton spins, F = I + s, gives the singlet F = 0 and the triplet F = 1.…”
mentioning
confidence: 99%